Design and political dissent spaces, visuals, materialities - Traganou, Jilly 1966- (Routledge, Taylor & Francis Group, 2021)
"This book examines, through an interdisciplinary lens, the relationship between political dissent and processes of designing. In the past twenty years, theorists of social movements have noted a diversity of visual and performative manifestations taking place in protest, while the fields of design, broadly defined, have been characterized by a growing interest in activism. The book's premise stems from the recognition that material engagement and artifacts have the capacity to articulate political arguments or establish positions of disagreement. Its contributors look at a wide array of material practices generated by both professional and nonprofessional design actors around the globe, exploring case studies that vary from street protests and encampments to design pedagogy and community-empowerment projects. For students and scholars of design studies, urbanism, visual culture, politics and social movements, this book opens up new perspectives on design and its place in contemporary politics"--
Keywords: Visuelle Kommunikation; Politische Auseinandersetzung; Communication in design; Art and social action; Aufsatzsammlung